2014
DOI: 10.1002/14651858.cd001478.pub6
|View full text |Cite
|
Sign up to set email alerts
|

Acellular vaccines for preventing whooping cough in children

Abstract: Background Routine use of whole-cell pertussis (wP) vaccines was suspended in some countries in the 1970s and 1980s because of concerns about adverse e ects. Following this action, there was a resurgence of whooping cough. Acellular pertussis (aP) vaccines, containing purified or recombinant Bordetella pertussis (B. pertussis) antigens, were developed in the hope that they would be as e ective, but less reactogenic than the whole-cell vaccines. This is an update of a Cochrane review first published in 1999, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 101 publications
2
51
0
5
Order By: Relevance
“…Efficacy also varies between aP products. A 2011 Cochrane review found aP vaccines containing ‡3 components provide greater protection than aP vaccines with fewer components [61]. Thus when considering the comparative effectiveness of aP and wP vaccines, the heterogeneity in products needs to be considered.…”
Section: Wp and Ap Efficacy And Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficacy also varies between aP products. A 2011 Cochrane review found aP vaccines containing ‡3 components provide greater protection than aP vaccines with fewer components [61]. Thus when considering the comparative effectiveness of aP and wP vaccines, the heterogeneity in products needs to be considered.…”
Section: Wp and Ap Efficacy And Effectivenessmentioning
confidence: 99%
“…Thus when considering the comparative effectiveness of aP and wP vaccines, the heterogeneity in products needs to be considered. Considering the limited and variable efficacy and effectiveness data available for wP vaccines, the Cochrane review concluded that ‡3 component aP were more effective than low-efficacy wP vaccines, but may be less effective than the highest-efficacy wP vaccines [61]. Efficacy and effectiveness studies for aP and wP vaccines have varied in design, case definition, case ascertainment, vaccination schedule and period of follow-up, limiting the ability to directly compare results between studies [57].…”
Section: Wp and Ap Efficacy And Effectivenessmentioning
confidence: 99%
“…The first studies published described HHE following a whole-cell pertussis vaccine [1][2][3] ; a Cochrane review 11 showed that the risk of hypotonic-hyporesponsive episodes was significantly lower in acellular vaccine recipients compared with those immunised with whole-cell vaccines. Our cohort did not allow us to make a comparison between the 2 vaccines, but seems to confirm that the cellular pertussis components are not the only factor involved in HHE.…”
Section: Discussionmentioning
confidence: 99%
“…Protective efficacy is defined as prevention of infections, as defined, occurring 30 days after the third immunization. Systematic reviews have shown that three-and five-component acellular vaccines are equally or more effective than whole-cell vaccines against pertussis, which in turn are more effective than one-or two-component acellular vaccines (Zhang et al, 2012). Thus, systemic immunization with acellular pertussis vaccines incorporating multiple virulence factors involved in adherence and mucosal infection have clinical efficacy against B. pertussis infection comparable or superior to that provided by the killed whole-cell vaccine.…”
Section: Vaccinementioning
confidence: 99%